Time pressure alters takeoff but not landing biomechanics in single-leg countermovement jumps - Ugur Yilmaz; Huseyin Celik; Pinar Arpinar-Avsar (PLoS ONE, 2025)
This study examined how time pressure influences lower-limb biomechanics during single-leg maximal countermovement jumps (CMJs), with a focus on kinetic and kinematic responses during both jumping and landing phases. Participants performed single-leg CMJs under two conditions: self-paced (SP) and reaction-time (RT), the latter simulating time-constrained environments. Joint angles, ground reaction forces (vGRF), and joint moments were analyzed. Significant differences emerged between SP and RT tasks in jumping-phase kinetics and kinematics, with only kinematic differences present during landing. The RT condition led to reduced hip and knee flexion, increased peak vGRF, and shorter flight times, yet no improvement in jump height. This suggests inefficient energy transfer possibly due to reduced range of motion and increased muscle co-contraction or pretension strategies. Joint moment analysis revealed a shift from a hip-dominant strategy in SP to a knee-dominant strategy in RT. Landing in RT was characterized by reduced joint flexion and increased frontal plane loading, potentially elevating the risk of lower-limb injury. Time pressure modifies motor strategies in single-leg CMJs, promoting faster execution at the cost of performance efficiency. These findings underscore the importance of training for both explosive performance and neuromuscular control under time-constrained, sport-specific conditions.